THE LEARNING PROCESS OF PHYSICAL AND HEALTH EDUCATION SUBJECT IN CLASS VIII OF SMP N 4 KOTA PAYAKUMBUH - Firdaus, Kamal (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The problem of this research was initiated by the learning process of Physical, Sport and Health Education which was not run well. This research was aimed at revealing the students intrinsic and extrinsic motivation toward the learning process of Physical, Sport and Health Education subject at SMP N 1 Kota Payakumbuh. This was a descriptive research. The population of the research was all of students (287) in grade VIII of SMPÂ N 4 Kota Payakumbuh. By using random sampling technique, 20% (55 students) of the population were taken as the sample. The data were obtained by making use of the questionnaire of Gudmans scale. The data gathered then were analyzed by using statistic of descriptive percentage. Based on the results of data analysis, it was figured out that: 1) the students intrinsic motivation toward Physical, Sport and Health Education subject at SMP N 4 Kota Payakumbuh is 44.6% (average), and 2) the students extrinsic motivation toward Physical, Sport and Health Education subject is 41.8% (average). From these results, it is concluded that the students motivation toward Physical, Sport and Health Education subject, in general, is in average category.